Protecting Cattle and Buffaloes from Haemorrhagic Septicaemia - Shivachandra, Sathish B. (Indian Farming, 2015)
Despite the annual vaccination of cattle and buffaloes against HS in most regions of India, the disease continues to be the major threat to the health scenario of livestock. To address the existing challenges and constraints in tackling the menace of HS in Indian subcontinent, a strategic control measures with a focus on key areas such as mandatory disease reporting, specific and rapid disease diagnosis coupled with implementation of mass vaccination programmes with an effective vaccine, should be strictly implemented. Moreover, with the support from International animal Corrigendum In the May 2014 issue of Indian Farming, in the Table of Contents at Page 1 â€“ the article titled â€œManagement of Change Inspired by NAIPâ€, authored by C. Devakumar et al., page 41, has been printed under the sub-heading Livelihood Security Options. Itâ€™s correct place is under the previous sub-heading, i.e. the last article under Lessons from PIU. health organizations, national level activities should be stepped up with a concerted collaboration with regional and state departments, which would help to control the HS in India. Alternatively, attempts are being made through conventional and molecular approaches to better understand the pathogen and its virulence factors, pathogenicity, host specificity, immunogens, determinants of protective immunity, cross protective antigens as well as diversity among Indian strains of P. multocida.